Row houses : a housing typology. - Pfeifer, Günter, 1943-; Brauneck, Per, ....- (Basel : Birkhäuser, 2008)
This fascinating book explores the potential to create a variety of building types in the modern urban area. To continue developing existing building types in an intelligent way is a crucial task in the field of residential building. A deeper understanding of the underlying types is indispensable for the success of the individual design, as well as for ensuring that tried and tested structures can be utilized, repeated, and varied in a wide variety of situations. For this typology of residential buildings, the authors have developed systematic new presentations of the most innovative types. Each volume lays out the possibilities for using and transforming a particular form of residential structure. The first volume deals with the various types of the courtyard house, which utilizes the courtyard as an intimate outdoor living space. The second volume is devoted to the various types of row house, a particularly widespread form of residential structure. Within each type, variants are distinguished according to how they organize space, their number of floors, and other criteria. The range of possible solutions is presented in uniform ground plans newly drawn to scale.
Keywords: Woningbouw